2005
DOI: 10.1093/jnen/64.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Anatomical, and Biochemical Events Associated with Neurodegeneration in Mice with Niemann-Pick Type C Disease

Abstract: In Niemann-Pick type C (NPC) disease, cholesterol associated with either apoE or apoB100 is taken up by cells in all tissues, including the central nervous system, through clathrin-coated pits and becomes trapped in late endosomes and lysosomes. This study defines the functional, biochemical, and molecular events that ensue as nerve cell death occurs. In mice homozygous for a mutation in NPC1, neuromuscular dysfunction begins at 5 weeks and death occurs at 13 weeks of age. Cholesterol accumulates in every tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 52 publications
12
95
0
1
Order By: Relevance
“…24 In agreement with previous reports, the NPC mut/mut sample showed a large accumulation of microglia with the typical amoeboid morphology characteristic of activated cells, whereas only ramified (resting) microglia were seen in NPC WT/WT animals. 4,22,25 However, there was no obvious difference in NPC mut/mut mice with or without expression of the Rab9 transgene in either 7-or 10-week-old animals (data not shown). ii) Weight loss.…”
Section: Resultsmentioning
confidence: 89%
“…24 In agreement with previous reports, the NPC mut/mut sample showed a large accumulation of microglia with the typical amoeboid morphology characteristic of activated cells, whereas only ramified (resting) microglia were seen in NPC WT/WT animals. 4,22,25 However, there was no obvious difference in NPC mut/mut mice with or without expression of the Rab9 transgene in either 7-or 10-week-old animals (data not shown). ii) Weight loss.…”
Section: Resultsmentioning
confidence: 89%
“…The main biochemical manifestation of NPC pathology is the abnormal accumulation of free cholesterol and glycosphingolipids within the endosomal-lysosomal system in various brain regions, including cortex, hippocampus, and cerebellum (13,14,62,63). The hydrophobic amine, U18666A (3-␤-[2-(diethylamino) ethoxy]androst-5-en-17-one), is a well known class II amphiphile, which has been shown to trigger accumulation of cholesterol by inhibiting its intracellular transport, as observed in NPC pathology (22).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that dysfunction of the NPC1 protein can lead to intracellular accumulation of cholesterol and degeneration of neurons in selected regions of the brain, but the underlying mechanisms remain unclear (13,62,63). Some recent studies have indicated that deregulation of the phosphatidylinositol 3-kinase pathway (93), A␤-mediated signaling cascades (20,21), or increased levels/activity of cathepsins (24,30) may contribute to the loss of neurons in NPC1 knock-out mouse brains.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that severe loss of neurons/ terminals in Npc1 Ϫ/Ϫ mice is evident largely in the cerebellar Purkinje cells, whereas hippocampal neurons are relatively spared. [13][14][15]18 At present, the cell death mechanism remains unclear as events related to both apoptosis and autophagy have been identified in Npc1 Ϫ/Ϫ mouse brains. Detection of terminal deoxynucleotidyl transferase dUTP nick-end labeling-positive and active caspase-3-immunoreactive Purkinje cells 62,63 is consistent with cell death being due to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive loss of neurons is particularly evident in the prefrontal cortex, thalamus, brainstem, and cerebellum but not in the hippocampal formation. [13][14][15][16][17][18] However, at present, very little is known about the underlying mechanisms associated with the vulnerability of select populations of neurons in Npc1 Ϫ/Ϫ mice. A number of earlier studies have shown that the EL system, the major site of cholesterol accumulation in NPC pathology, consists of two dynamic interrelated cellular pathways: the endocytic pathway and the lysosomal system.…”
mentioning
confidence: 99%